Potensi munculnya kerentanan sosial akibat transmisi covid-19 pada upacara adat dan urgensi pendidikan kritis-higienik - Marianus Mantovanny Tapung; Marianus Supar Jelahut (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
This phenomenological research aims to examine the potential for the spread of Covid-19 at every traditional ceremony, and the emergence of escalations that have an impact on social vulnerability in Manggarai. In addition, this study aims to examine the urgency of critical hygiene education for the community so that they are wiser and wiser when participating in social activities, and have critical awareness to apply health protocols and behave in a healthy and clean life. This study uses a critical phenomenological method with the stages of exploring the experiences or social actions experienced by the Manggarai people when they are in a Covid-19 pandemic situation, especially related to clean and healthy living behavior, then analyzing the causes. The conclusion in this study is that although traditional ceremonies remain an inseparable part of the lives of the Manggarai people because of their various noble goals, the form of crowds during the Covid-19 pandemic has the potential to accelerate the transmission of the virus. Corona virus transmission can be through contact with body parts, saliva splashes, cutlery and drinking utensils, animal victims, dowry items, etc. For this reason, it is the duty and responsibility of the local government and the community to always make the public aware by making rules, socialization, promotion of dissemination and critical-hygienic education about the dangers of Covid-19 and the importance of following health protocols, such as reducing crowds, maintaining distance, wearing masks, and washing hands.